Analysis of Financial Performance in Realizing Good University Governance (Study at Manado State University) - Kawatu, Freddy Semuel; Tumiwa, Ramon Arthur Ferry; Kewo, Cecilia Lelly (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2020)
Financial management reform in university is an effort to realize good university governance in financial management. The research objective was to determine the financial performance of the Manado State University Institution, and how to reform financial management as an effort to achieve Good Governance. The research method used in this research is descriptive qualitative with the type of data qualitative data. The data source uses secondary data obtained from the Financial Statements of Manado State University for Fiscal Year 2017 - 2019. The data analysis technique used a qualitative approach with descriptive methods. This study proves that the good governance of the Manado State University has implemented financial management following Government Regulation Number 71 of 2010 and is of higher quality by taking into account the determinants of financial performance.